Exploring Out-of-Class English Frequency and Preferences A Students - Wiriya, Pinyada (Chophayom Journal, 2024)
Out-of-class English language learning plays a crucial role in enhancing language proficiency and fostering learner autonomy (Benson, 2011). Moreover, it allows students to take control of their language learning journey and develop lifelong skills beyond traditional classroom settings. This study investigated the frequency and preference of out-of-class English learning activities among English major students at Rajabhat Maha Sarakham University, Thailand. Applying purposive sampling, 249 students participated in the survey. A questionnaire, adapted from Cheng (2015) and Sun (2016) and translated into Thai, was employed. The analysis included the calculation of mean and standard deviation, with interpretation based on the Likert scale. The findings revealed that participants demonstrated a moderate frequency of participation in out-of-class activities. In terms of preferences, participants showed a neutral level of preference for out-of-class English learning activities. In conclusion, the findings suggest that students should be encouraged to engage in out-of-class English language learning by suggesting different activities. It is important to find a balance between what students like and what they don't like for better language learning outside of the regular class. Keywords: out-of-class activities, English language learning, English major students